THE THE ROLE OF THE TEACHER AS A FACILITATOR IN THE USE OF INDONESIAN IN ELEMENTARY SCHOOL - Marwanto Marwanto (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2021)
This study discusses the role of the teacher as a facilitator of the use of Indonesian in the learning process. The teacher is a very important person in the world of education in the teaching and learning process as a mediator, facilitator, and leader in the classroom. Teachers and students must be able to communicate well as the principle of communication between teachers and students so that learning runs well. Even during a pandemic like now. Teachers are required to be more varied and wise in learning and to form closeness with students. The focus of this research is how the teacher's role as a facilitator of the use of Indonesian in Elementary School. Study on the use of Video Calls in Class 1 Learning at Muhammadiyah Elementary School Plus Salatiga. This study used interview, documentation, and observation techniques with two teachers, two students, and two student guardians. This research uses descriptive qualitative research methods. In the first grade students of Muhammadiyah Plus Salatiga elementary school, Indonesian language learning is on the theme of one learning two, namely Understanding Guidance Sentences